(untitled) (Fiep Bulletin - online, 2015)
Many researchers around the world using different dimensions and proposals have studied Capoeira. However, some aspects involving the physical practices still require more critical comments. Capoeira is an important intangible heritage of the country and part of the history and of Afro-Brazilian culture. This practice took on a new role in the school perspective, especially after the enactment of Law n. 10.639/2003. In this sense, the relations amongst Capoeira and school became an important topic of study. This paper aims to present a theoretical framework that discusses the importance of body practices as an element for identity construction, using as a starting point the relationships between the concepts of identity and territory. Surveys and theoretical debates showed that issues related to the process of identity construction derived from two concepts: (1) territorial disputes; (2) the historical revival process, and the memories built around practices of "invented traditions". These processes are not a recent movement, being in fact on the historical trajectory of Capoeira in Brazil since the nineteenth century.